Differential Regulation of Salmonella typhimurium Type III Secreted Proteins by Pathogenicity Island 1 (SPI-1)-Encoded Transcriptional Activators InvF and HilA - Eichelberg, Katrin (American Society for Microbiology, 1999)
Salmonella enterica encodes a type III protein secretion system within a pathogenicity island (SPI-1) that is located at centisome 63 of its chromosome. This system is required for the ability of these bacteria to stimulate cellular responses that are essential for their pathogenicity. Expression of components and substrates of this system is subject to complex regulatory mechanisms. These mechanisms involve the function of HilA and InvF, two transcriptional regulatory proteins encoded within SPI-1. In this study, we examined the functional relationship between these two regulatory proteins. We found that strains carrying loss-of-function mutations in either hilA or invF differ in their ability to stimulate cellular responses. An S. typhimurium hilA mutant strain retained considerable signaling capacity that resulted in significant levels of internalization into host cells. In contrast, introduction of a nonpolar loss-of-function mutation in invF rendered S. typhimurium significantly impaired in its ability to enter host cells. Consistent with these different phenotypes, we found that HilA and InvF control the expression of different genes. HilA regulates the expression of components of the type III secretion machinery, whereas InvF controls the expression of type III secreted proteins encoded outside of SPI-1. We also found that the expression of secreted proteins encoded within SPI-1 are under the control of both HilA and InvF. Our results therefore indicate that InvF and HilA differentially control the expression of components and substrates of the invasion-associated type III secretion system.